Teorías de cohomología / Cohomology theories (2011)
En este trabajo se construirán la cohomología singular, la cohomología de Cech relativa a un buen cubrimiento y la cohomología de De Rham en manifolds suaves y se mostrará la equivalencia entre algunas de estas./Abstract: In this paper we will construct the singular cohomology, the Cech cohomology relative to a good cover and the De Rham cohomology in smooth manifolds and we will show the equivalence between some of these.